Basement membrane product, endostatin, as a link between inflammation, coagulation and vascular permeability in COVID-19 and non-COVID-19 acute respiratory distress syndrome - Jandl, Katharina; Berg, Johannes Lorenz; Birnhuber, Anna; Fliesser, Elisabeth; Borek, Izabela; Seeliger, Benjamin; David, Sascha; Schmidt, Julius J.; Gorkiewicz, Gregor; Zacharias, Martin; Welte, Tobias; Olschewski, Horst; et al. (Frontiers in Immunology, 2023)
Background Immune cell recruitment, endothelial cell barrier disruption, and platelet activation are hallmarks of lung injuries caused by COVID-19 or other insults which can result in acute respiratory distress syndrome (ARDS). Basement membrane (BM) disruption is commonly observed in ARDS, however, the role of newly generated bioactive BM fragments is mostly unknown. Here, we investigate the role of endostatin, a fragment of the BM protein collagen XVIIIα1, on ARDS associated cellular functions such as neutrophil recruitment, endothelial cell barrier integrity, and platelet aggregation in vitro. Methods In our study we analyzed endostatin in plasma and post-mortem lung specimens of patients with COVID-19 and non-COVID-19 ARDS. Functionally, we investigated the effect of endostatin on neutrophil activation and migration, platelet aggregation, and endothelial barrier function in vitro. Additionally, we performed correlation analysis for endostatin and other critical plasma parameters. Results We observed increased plasma levels of endostatin in our COVID-19 and non-COVID-19 ARDS cohort. Immunohistochemical staining of ARDS lung sections depicted BM disruption, alongside immunoreactivity for endostatin in proximity to immune cells, endothelial cells, and fibrinous clots. Functionally, endostatin enhanced the activity of neutrophils, and platelets, and the thrombin-induced microvascular barrier disruption. Finally, we showed a positive correlation of endostatin with soluble disease markers VE-Cadherin, c-reactive protein (CRP), fibrinogen, and interleukin (IL)-6 in our COVID-19 cohort. Conclusion The cumulative effects of endostatin on propagating neutrophil chemotaxis, platelet aggregation, and endothelial cell barrier disruption may suggest endostatin as a link between those cellular events in ARDS pathology.